Toxicological assessment and underlying mechanisms of tetrabromobisphenol A exposure on the soil nematode Caenorhabditis elegans. (March 2020) - Liu, Fuwen; Zhang, Ying; Zhang, Meng; Luo, Qishi; Cao, Xue; Cui, Changzheng; Lin, Kuangfei; Huang, Kai
Abstract: The widespread use of tetrabromobisphenol A (TBBPA) in industries has resulted in its frequent detection in environmental matrices, and the mechanisms of its associated hazards need further investigation. In this study, the nematode Caenorhabditis elegans (C. elegans) was exposed to environmentally relevant concentrations of TBBPA (0, 0.1, 1, 10, 100, 200 μg/L) to determine its effects. At TBBPA concentrations above 1 μg/L, the number of head thrashes, as the most sensitive physiological indicator, decreased significantly. Using the Illumina HiSeq™ 2000 sequencer, differentially expressed genes (DEGs) were determined, and 52 were down regulated and 105 were up regulated in the 200 μg/L TBBPA treatment group versus the control group. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database analysis demonstrated that dorso-ventral axis formation is related to neurotoxicity; metabolism of xenobiotics by Cytochrome P450 (CYP450) and glutathione-S-transferase (GST) was found to be the vital metabolic mechanisms and were confirmed by quantitative real-time polymerase chain reaction (qRT-PCR). GST was ascribed to the augmentation because mutations in cyp-13A7 were constrained under TBBPA exposure. Additionally, oxidative stress indicators accumulated in a dose-dependent relationship. These results will help understand the molecular basis for TBBPA-induced toxicity in C. elegans and open novel avenues for facilitating the exploration of more efficient strategies against TBBPA toxicity. Graphical abstract: Image 1 Highlights: Neurotoxicity of TBBPA to C. elegans by sensitive exposure. Head thrashes was the most sensitive neural indicator. CYP450 and GST pathways contributed to mitigating TBBPA-induced toxicity. Cyp-13A7 gene was deduced to assist nematodes response to TBBPA-induced toxicity.